Smart Medication Handling: Health Education on Beyond Use Date (BUD) and Proper Medication Storage at Muhammadiyah 5 Junior High School Samarinda: Cerdas Menyimpan Obat: Edukasi Kesehatan mengenai Beyond Use Date (BUD) dan Penyimpanan Obat yang Benar di SMP Muhammadiyah 5 Samarinda - Nurul Fitriani; Syaidati Nafi'atul Ummah; Rahayu Hastuti (Jurnal Abdita Naturafarm, 2026)
The Beyond Use Date (BUD) concept refers to the period of time a drug can be used immediately after it is formulated, prepared, or when its primary container is opened. On the other hand, the Expired Date (ED) indicates the shelf life of the drug from the factory before the packaging is opened. Both terms play a crucial role in maintaining the quality and safety of drug preparations. Information about the BUD is not always printed on the packaging by the pharmaceutical industry, pharmacists need to provide education on appropriate storage, including temperature and container type regulations, as well as determining BUD based on the dosage form, to maintain safety and prevent drug quality degradation. This knowledge is very important to understand from school age, including by junior high school students. The education was conducted using a lecture method using PowerPoint and leaflets as props. Evaluation mechanisms included pre-test and post-tests to measure participants' knowledge. All participants successfully understood and increased their knowledge of the Beyond Use Date (BUD) concept and proper medication storage, as evidenced by the improved average scores on the pre-test and post-tests.